KAJIAN KUALITAS LAYANAN JASA TRANSPORTASI LOGISTIK UNTUK MENINGKATKAN KEPUASAN PELANGGAN DENGAN PENDEKATAN METODE ZONE OF TOLERANCE (ZOT) - Armin Darmawan; Amrin Rapi; A Alief Rachmat (Jurnal Ilmiah Teknik Industri, 2021)
Logistics transportation service industries experiencing the growth significantly due to e-commerce growth since the last decade. However, services industry, it is difficult to quantify as it is a function of different user preference over time.  The study examined to evaluate the service satisfaction level of logistics service systems in order to develop service satisfaction more responsive, empathy, reliable and friendly. A survey conducted to users of logistics services provider in Makassar city. Kano model was the methodology used in evaluating the service satisfaction systematically by integrating attributes of logistics services based on service user preference into some clusters. ZOT (Zone of Tolerance) was proposed in mapping the level of service and prioritizing the improvement. The performance of the Logistics Services Quality (LSQ) was currently using attributes based on five dimensions of SERVQUAL. Measuring the quality of services carried out by comparison with the minimum values based on ZOT that was still acceptable and the quality of service that desired by users. Based on 20 attributes, the result showed three attributes that existed above MSS (Measure of Service Superiority) and seven attributes that existed below the MSA (Measure of Service Adequacy) that needed the improvement of the quality of services.